Evaluation of carbonyl collection methods in electronic cigarette aerosols - Martinez, Bianca; Son, Yeongkwon; Khlystov, Andrey (Frontiers in Chemistry, 2025)
IntroductionThis study evaluated the performance of three carbonyl collection media that are frequently used in electronic cigarette (e-cig) studies, namely: 2,4-Dinitrophenyl hydrazine (DNPH) silica impregnated cartridges (C), a DNPH-coated glass fiber filter (DF), and an impinger with a DNPH solution (I).MethodsThese collection methods were tested with a ‘mod’ and a ‘pod’ e-cigs that represent devices producing different amounts of e-cig aerosols. The tests were performed using two different puff topography regimes to investigate the effect of puff flow rate on carbonyl collection efficiency. Carbonyls emitted from the e-cigs were collected using I-I (two impingers in series), C (a single DNPH cartridge), and DF-C (a DNPH filter followed by a DNPH cartridge). Samples were analyzed using high-performance liquid chromatography coupled with photodiode array detector.ResultsMeasured carbonyl levels varied between the three methods. For both devices, the highest values were measured with C and DF-C. Results from the ‘pod’ device measured with I-I were comparable with the other methods, but lower than the other two methods for the ‘mod’ device. For example, 1 LPM ‘mod’ acetaldehyde emissions measured with C (0.09 ± 0.02 µg/puff) and DF-C (0.14 ± 0.09 µg/puff) were significantly higher (p = 0.06 and 0.04, respectively) than I-I method (0.05 ± 0.02 µg/puff).DiscussionThe likely cause for the underestimation by the I-I method is the inefficient collection of particle phase bound carbonyls by the impingers and, possibly, wall losses in the inlet of the impinger. Based on our results, C provides the best approach for carbonyl collection in e-cig aerosols, while I-I that is used in the standard testing method can underestimate carbonyl emissions when measuring high concentration aerosols such as those produced by ‘mod’ devices.